Laryngeal transplantation: from experimental feasibility to multidisciplinary clinical reality - Lu Zeng; Longhao Wang (Frontiers in Surgery, 2026)
Laryngeal transplantation represents one of the most complex forms of vascularized composite allotransplantation (VCA), aiming to restore respiration, phonation, and swallowing in patients with irreversible laryngeal dysfunction. Over the past decades, systematic preclinical research—including refinement of large-animal and rodent models, organ preservation optimization, and elucidation of immunological mechanisms—has laid the scientific foundation for clinical translation. Advances in static cold storage, emerging machine perfusion technologies, and biomarker-based precision monitoring have further improved graft viability and rejection surveillance. Clinically, since the first successful human laryngeal transplantation in 1998, approximately 16 cases worldwide have demonstrated the feasibility of long-term graft survival and meaningful functional recovery. More recently, indications have expanded from trauma-related defects to carefully selected oncologic patients under rigorous immunological and ethical oversight. Surgical progress has focused on microvascular reconstruction, selective neural reinnervation, and airway stabilization, while postoperative management emphasizes individualized immunosuppression, structured rehabilitation, infection prophylaxis, and lifelong surveillance for rejection and malignancy. Nonetheless, major challenges persist, including chronic rejection, variability in functional outcomes, oncologic safety under immunosuppression, donor scarcity, and unresolved ethical issues in a non–life-saving transplant context. Future directions center on integrating multi-omics biomarkers, machine-learning–based monitoring, bioengineered scaffolds, and personalized immunomodulation to enhance long-term graft function and safety. Overall, laryngeal transplantation has evolved from experimental feasibility to a clinically realistic reconstructive strategy, yet its broader application will depend on multidisciplinary innovation and rigorous ethical governance.